Revolution or Ruin? Systematic Insights into the Redefinition of the Teacher Book - Widi Pratolo, Bambang; Anwari, Hamdan; Purwanti, Eko; Fatimah, Nur; Soviyah, Soviyah; Nuryana, Zalik (English Language Teaching Educational Journal, 2025)
This study investigates the redefinition of the teacher book across nearly two decades (2006-2025) with the objective of tracing its conceptual evolution, theoretical contestations, and disciplinary reinterpretations. The research employed a systematic literature review following the PRISMA 2020 protocol, focusing on Scopus-indexed publications. An initial 74 records were identified, and after applying inclusion criteria (English-language, open access, research articles), 28 documents were analysed as the final corpus.The results indicate that the teacher book has undergone three significant shifts: (1) its early construction as a prescriptive instrument ensuring curricular compliance but constraining teacher creativity, (2) its contestation as both a pedagogical guide and a barrier to teacher autonomy within the discourse of innovative and student-centered learning, and (3) its transformative reinterpretation as a digital and cultural artefact, enabling collaborative, reflective, and context-based teaching practices. This trajectory illustrates that the teacher book operates not merely as a technical manual but as a dynamic discursive field where educational ideologies and practices intersect.Research implications highlight the necessity of situating the teacher book within critical pedagogy, constructivism, and digital literacy frameworks, as well as recognizing its dual role in reinforcing and challenging educational orthodoxies. Practical implications underline the need for teachers to adopt adaptive and critical use of teacher books, for curriculum designers to integrate technological and cultural responsiveness into their development, and for policymakers to encourage evidence-based resources that support creativity, critical thinking, and 21st-century competencies.